IoT based intelligent wireless substation monitoring and controlling system - Khan, Serajul Islam; Abdullah, S.M.Sifat; Alam, Jawad Bin; Das, Pramit (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.